Sistem Informasi Arsip Terpadu LPP TVRI Stasiun Kalimantan Selatan - Setiawan, Heru; Nijam Akbar, Muhammad (Journal Information Technology Trends (JITRENDS), 2024)
The research discusses the development of an Information System for LPP TVRI StasiunKalimantan Selatan, which faces challenges such as paper shortages, stationery conservation,and direct mail delivery, leading to delays in mail validation when officials are on business trips.To address these issues, the development of an internal mail management system is consideredcrucial to enhance service efficiency at TVRI Stasiun Kalimantan Selatan. The objective of thisdevelopment is to build an Integrated Archive System for LPP TVRI Stasiun Kalimantan Selatan.The method used in the system development is the waterfall method. The results fromimplementing this system show that mail management has become more efficient. In conclusion,this system facilitates TVRI Stasiun Kalimantan Selatan in managing incoming and outgoing mail,thereby improving services more effectively and quickly..